Modulation of neuronal nitric oxide synthase and apoptosis by the isoflavone genistein in Mdx mice. (31st August 2015) - Messina, Sonia; Bitto, Alessandra; Vita, Gian Luca; Aguennouz, M'hammed; Irrera, Natasha; Licata, Norma; Sframeli, Maria; Bruschetta, Daniele; Minutoli, Letteria; Altavilla, Domenica; Vita, Giuseppe; Squadrito, Francesco
Abstract Dystrophin lack in DMD causes neuronal nitric oxide synthase (nNOS) membrane delocalization which in turn promotes functional muscle ischemia, and exacerbates muscle injury. Apoptosis and the exhaustion of muscle regenerative capacity are implicated in Duchenne muscular dystrophy (DMD) pathogenesis and therefore are relevant therapeutic targets. Genistein has been reported to have pro‐proliferative effects, promoting G1/S cell phase transition through the induction of cyclin D1, and anti‐apoptotic properties. We previously showed that genistein could reduce muscle necrosis and enhance regeneration with an augmented number of myogenin‐positive satellite cells and myonuclei, ameliorating muscle function in mdx mice. In this study we evaluated the underlying mechanisms of genistein effect on muscle specimens of mdx and wild type mice treated for five weeks with genistein (2 mg/kg/i.p. daily) or vehicle. Western blot analysis show that genistein increased cyclin D1 and nNOS expression; and showed an antiapoptotic effect, modulating the expression of BAX and Bcl‐2. Our results suggest that this isoflavone might enhance the regenerative spurt in mdx mice muscle restoring nNOS, promoting G1/S phase transition in muscle cell, and inhibiting apoptosis. Further studies with longer time treatment or using different experimental approaches are needed to better investigate the underlying mechanisms of such results. © 2015 BioFactors, 41(5):324–329, 2015